Image encryption and decryption using computer generated holography - Istiaque, Md. Asif; Mahi, Md. Mainul Islam; Hasan, Syed Aousaf (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.